Cancer and Anorexia Nervosa in the Adolescence: A Family-Based Systemic Intervention. (14th July 2011) - De Benedetta, Gabriella; Bolognini, Ida; D'Ovidio, Silvia; Pinto, Antonello
Abstract : Objective . Anorexia nervosa is difficult to diagnose in cancer patients since weight loss, aversion for food, and eating disturbances are frequent in patients undergoing chemotherapy and radiotherapy. Nevertheless, efforts are mandatory to recognize and manage this condition which may occur also in cancer patients with a special regard to adolescents. Methods . Through the clinical history of Anna, a 15-year-old adolescent with advanced cancer, we describe the effectiveness of a family-based systemic intervention to manage anorexia nervosa occurring in concomitance to osteosarcoma. Results . Through a two-year psychotherapy period involving different techniques applied to the whole family such as family genogram, family collage, and sculpture of family time, Anna was relieved from her condition. Conclusions . Upon early diagnosis and appropriate treatment, anorexia nervosa can be effectively approached in adolescent cancer patients. The presence of a life-threatening medical condition such as cancer may provide motivation for a patient to control disordered eating behavior in the context of an appropriate family-based systemic intervention. The general frame of anorexia occurring in cancer-bearing adolescents is reviewed and discussed.